Digital Analysis: The Impact of Kenya's Insolvency Act, 2015 on Secured Creditor's Security Realization. - Jane Juma,; Charles Ochieng' Oguk, (IJRDO - Journal of Business Management, 2025)
This article analyzes the impact of the Kenya's Insolvency Act, 2015 (the Act) on the efficiency and predictability of secured creditors' ability to realize their security interests in digital age. It critically examines key provisions of the Act, relevant case laws, and highlights identified procedural ambiguities and systemic impediments that deviate from the Act's objectives of establishing a clear, efficient, and equitable framework balancing debtor rehabilitation and predictable security realization. The study draws upon existing legal research and comparative analysis with international insolvency regimes. While the Act aims to protect creditor rights, the introduction of debtor rescue mechanisms and practical implementation challenges, including the lack of comprehensive empirical data and limited integration of digital tools, potentially undermine the anticipated ease and cost-effectiveness of security realization. The article explores the potential role of digital technologies, including data analytics and Artificial Intelligence (AI), in enhancing transparency, predictability, and efficiency within the insolvency process, particularly concerning data management and decision support for security realization.